Cezanne - Richter, Jochen.Mullins Edwin; Hausmann, Jacob (s.l. Glashaus Film Production in association with RM Arts, 1985)
Shunned and neglected by artists and critics of his time, Cezanne retreats to his birthplace, Air-en-Provene, where he spends the rest of his life as a racluse. Here the treks the forests and mountains in which he finds the inspiration to achieve his greatest works. His works have influenced many of the major artists of the 20th century, canning him the title "Father of Modern Art".
VHS.
Andre Danes as Paul Cezanne.
Keywords: Cezanne, Paul, 1839-1906.; Painters -- Frances -- Biography; Impressionisr artists -- France